123k views
2 votes
Use geometric model to factor x2+3x+2

2 Answers

3 votes

Answer:

-1 and -2

Explanation:

x ²+3x+2 = 0

We can solve the expression by first factorizing.

Factorizing by splitting the middle term

we look for 2 numbers that when multiplied will be +2 and when added it will be +3+2 and +1 = +3 and 2 ( these is correct because it is the same as the question asked)

-2 and -1 = -3 and 2

x²+2x+x+2 = 0

x(x+2)+1(x+2) =0

(x+1)(x+2)= 0

x+1 = 0 x+2=0

x= -1, x= -2

x = -1 and -2

User Nathan A
by
4.7k points
7 votes

Answer:

-1 and -2

Step-by-step explanation:x ²+3x+2 = 0

x²+2x+x+2 = 0

x(x+2)+1(x+2) =0

(x+1)(x+2)= 0

x+1 = 0 x+2=0

x= -1, x= -2

x = -1 and -2

User Agiliq
by
5.1k points